English in mind. - Puchta, Herbert (Cambridge University Press, 2010)
This brand new edition of English in Mind revises and updates a course which has proven to be a perfect fit for classes the world over. Engaging content and a strong focus on grammar and vocabulary combine to make this course a hit with both teachers and students. --Book Jacket.